Attitudes and perceptions of traditional health practitioners towards documentation of patient health information in their practice in eThekwini Municipality, KwaZulu-Natal, Natal Province, South Africa. Issue 1 (January 2023) - Zhandire, Tracy; Gqaleni, Nceba; Ngcobo, Mlungisi; Gomo, Exnevia
Background: Documentation of patient health information in the form of patient medical records (PMRs) is an essential, ethical and regulatory requirement in any healthcare system. African traditional medicine (ATM) exists parallel to biomedicine and continues to play a significant role in primary healthcare of the majority of South Africans. The World Health Organization (WHO) has promoted the integration of ATM into the national health system of South Africa. Patient health information documentation can facilitate this integration, and PMRs promote communication between the two health systems through referrals. Documentation in biomedicine is a clear, compulsory, routine activity, but does not occur regularly or routinely in ATM. Objective: To examine the attitudes and perceptions of traditional health practitioners (THPs) towards documentation of patient health information in their practice. Methods: This quantitative cross-sectional survey involved snowball sampling to recruit THPs in Umlazi Township and rural parts surrounding the township, in Durban, South Africa. A semi-structured questionnaire was used. Quantitative data were analysed using SPSS 25 and the Relative Importance Index (RII) and qualitative data were analysed using Excel for themes. Results: Sampling resulted in 248 THPs of whom 178 (72%) were females. The RII ranked the factors that negatively influenced the participants' attitudes towards documentation of patient health information. Of the 178 females who participated in the study, 129 (72.5%) showed their willingness to introduce documentation in their practice. Of the 127 participants with less than 10 years of practice experience, 126 (99.2%) agreed to the importance of introducing PMRs in their practice. The majority of participants perceived documentation of patient health information as vital to improve their practice. A prominent theme was that the THPs regarded documenting patient health information as important and effective in their practice. Conclusion: More than half of participants showed positive attitudes and perceptions towards documenting of patient health information in ATM. The majority of the participants in this study acknowledged the importance of introducing documentation of patient health information in their practice even though they lacked experience and more knowledge. This reflects a need for essential intervention in developing specialised tools to begin promoting documentation of patient health information in ATM.